2021
DOI: 10.3390/ma14081848
|View full text |Cite
|
Sign up to set email alerts
|

A State of the Art of the Overall Energy Efficiency of Wood Buildings—An Overview and Future Possibilities

Abstract: The main goal of this study was to review current studies on the state of the art of wood constructions with a particular focus on energy efficiency, which could serve as a valuable source of information for both industry and scholars. This review begins with an overview of the role of materials in wood buildings to improve energy performance, covering structural and insulation materials that have already been successfully used in the market for general applications over the years. Subsequently, studies of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 176 publications
(228 reference statements)
1
10
0
Order By: Relevance
“…This shows that environmental sustainability cannot be achieved without strong emphasis on energy efficiency and use of renewable sources. This finding is in line with the findings of many studies, e.g., [5,8,9,23,30]. LEED, BREEAM or other sustainability certifications are gaining popularity worldwide as it helps to prove that a building is built in a sustainable manner and meets international or global environmental standards.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This shows that environmental sustainability cannot be achieved without strong emphasis on energy efficiency and use of renewable sources. This finding is in line with the findings of many studies, e.g., [5,8,9,23,30]. LEED, BREEAM or other sustainability certifications are gaining popularity worldwide as it helps to prove that a building is built in a sustainable manner and meets international or global environmental standards.…”
Section: Discussionsupporting
confidence: 89%
“…Timber construction is increasingly being proposed as a way to preserve nature and create a sustainable environment. Use of timber reduces the environmental impact of a building for several reasons: (1) wood is the only renewable construction material that requires very little energy for its processing; (2) all timber products store carbon; (3) timber emits less greenhouse gases in the production process and does not emit CO 2 during the lifetime of the building; (4) timber products are reusable and recyclable [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of sustainably sourced mass-timber technologies to build multistory residential buildings (mainly cross-laminated timber (CLT) and glue-laminated timber (glulam)) has the potential to mitigate global climate change and benefit developing economies [1][2][3]. While it is well known that the building sector is responsible for about 40% of global carbon emissions [4], there is a large body of scientific research showing that, compared to reinforced concrete (RC), mass-timber (MT) buildings can store large amounts of biogenic carbon, reduce the embodied carbon of building materials, and avoid useful life emissions from auxiliary space-conditioning energy [5][6][7][8]. In recognizing these advantages, large forest product exporters, such as China (CN), Brazil (BZ), and Chile (CL), are currently seeking synergies with their timber sector to tackle large housing deficits and meet carbon emission targets by 2050 [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Bio-based materials have recently become popular in the building and construction industry due to their insulation and hygroscopic properties [ 10 , 11 ]. Studies have reported that using these materials in construction increases the energy efficiency of the building and provide a comfortable and healthy indoor environment [ 12 , 13 , 14 ]. Some bio-based materials also have the ability to absorb and release moisture with respect to changing relative humidity levels, which can reduce the load on air conditioning and have a positive impact on wellbeing of residents [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%